2016
DOI: 10.5301/jabfm.5000324
|View full text |Cite
|
Sign up to set email alerts
|

Is Micro-Computed Tomography Useful for Wear Assessment of Ceramic Femoral Heads? A Preliminary Evaluation of Volume Measurements

Abstract: In conclusion, the findings of the present study suggest that this new protocol could be considered an important tool for wear assessment and that we have found a reliable metrological protocol for volumetric analysis of ceramic femoral head prostheses, demonstrating that the micro-CT technique can be an important tool for wear assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Numerous techniques have been developed to assess polyethylene wear in TKPs during simulator trials and retrieval studies [2] but these are associated with certain limitations. Recently, the use of micro-CT imaging has become widespread, including for wear assessment in retrieved polyethylene liners [10,15,16,27]. In this study, we sought to validate the use of advanced 3D optical scanning techniques to experimentally establish the areas most affected by wear in order to gather basic information to allow a better design of prosthetic knee joints in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous techniques have been developed to assess polyethylene wear in TKPs during simulator trials and retrieval studies [2] but these are associated with certain limitations. Recently, the use of micro-CT imaging has become widespread, including for wear assessment in retrieved polyethylene liners [10,15,16,27]. In this study, we sought to validate the use of advanced 3D optical scanning techniques to experimentally establish the areas most affected by wear in order to gather basic information to allow a better design of prosthetic knee joints in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Engh et al [14] used a micro-CT technique to quantify the polyethylene wear on retrieved knee components and they found that the micro-CT technique can determine the volume and location of the wear of retrieved tibial liners. Recently, Parrilli and co-workers [15] used a micro-CT technique to measure the volume loss from ceramic femoral heads. Affatato et al [16] validated a micro X-ray computed tomography technique to assess the wear of different commercially available, polyethylene’s acetabular cups after wear simulation.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement, Engh et al [41] used a μCT technique to quantify the polyethylene wear on retrieved knee components, and they found that this technique can determine the volume and location of wear of retrieved tibial liners. Recently, Parrilli and coworkers used a μCT technique to assess the volume loss of a femoral head and found that this “new protocol could be considered an important tool for wear assessment” [42]. In a recent work, Affatato et al [21] found a good correlation between μCT and gravimetric volumetric wear measurements performed on polymeric hip inserts, with wear volumes ranging from 6 to 25 mm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro wear evaluation of joint components is mainly performed using the gravimetric method, which is considered the gold standard [21,22]. Currently, advanced imaging techniques are also available, like high-resolution tomography, which allows nondestructive evaluation of the internal structures of the object.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, advanced imaging techniques are also available, like high-resolution tomography, which allows nondestructive evaluation of the internal structures of the object. Micro-computed tomography (µ-CT) is one of the most versatile non-invasive techniques in the medical field [22,23]. It is able to image internal biological structures without specific sample preparation and could help to overcome the limitation of the gravimetric method.…”
Section: Introductionmentioning
confidence: 99%